Isolation and identification of endophytic fungi connected to Grapevine Diseases, from the Tokaj wine region, Hungary - Kovács, Csilla; Peles, Ferenc; Hongtao, Xie; Szojka, Anikó; Hajdú, Gréta; Bihari, Zoltán; Sándor, Erzsébet (Acta Agraria Debreceniensis, 2014)
Grapevine Trunk Diseases (GTD) is one of the most important diseases in vineyards worldwide, which can be found in Hungarian vineyards as well. In Hungarian wine regions there is very little information about the occurrence of pathogens which cause GTD, in case of Tokaj wine region there is no knowledge about that, what kind of pathogens can be found in the vineyards.The objective of our research is to assess the situation and occurrence of GTD in Tokaj wine region in cooperation with local specialists, as well as identification of pathogens which were isolated from the diseased trunks by morphological and genetic basis.We were able to isolate endophytic fungi from all sampled grape trunk. The majority of them were determined as Diplodia seriata not only based on colony morphology, but also determined by rDNA sequences.